Lateral flow test engineering and lessons learned from COVID-19 - Budd,J; Miller,BS; Weckman,NE; Cherkaoui,D; Huang,D; Fongwen,N; Han,G-R; Broto,M; Estcourt,CS; Gibbs,J; Pillay,D; Sonnenberg,P; et al. (Nature Reviews Bioengineering, 2023)
The acceptability and feasibility of large-scale testing with lateral flow tests (LFTs) for clinical and public health purposes has been demonstrated in the COVID-19 pandemic. LFTs can detect analytes in a variety of samples, providing a rapid read-out, which allows self-testing and decentralised diagnosis. In this Review, we examine the changing LFT landscape with a focus on lessons learned from COVID- 9. We discuss implications of LFTs for decentralised testing of infectious diseases, including diseases of epidemic potential, the ‘silent pandemic’ of antimicrobial resistance, and other acute and chronic infections. Bioengineering approaches will play a key role in increasing the sensitivity and specificity of LFTs, improving sample preparation, incorporating nucleic acid amplification and detection, andenabling multiplexing, digital connection and green manufacturing, with the aim to create the next generation of highly-accurate, easy-to-use, affordable and digitally-connected LFTs. We conclude with recommendations, including the building of a global network of LFT research and development hubs tofacilitate and strengthen future diagnostic resilience.